Politics, power and ideology in American comedy late night talk shows: A critical discourse analysis - Al-Mnaseer, Farah Abdul-Jabbar Mahdi (2013)
There appears to be a new trend in transferring political issues through late night talk shows (LNTSs). The President of the United States, Barack Obama, displayed different types of power relations and political ideologies during the interviews despite the comedic nature of LNTSs. Although studies have been done on the relation between LNTSs and political discourse, only a limited number of studies have looked at theportrayal of power in LNTSs. The purpose of this study is to investigate Obama's bases of power, his power relations and his use of deixis to present his political ideologies in the two American LNTSs; The Late Show with David Letterman and The Tonight Show with Jay Leno. This study focuses on Obama's portrayal of power in his political discourse (PD) using critical discourse analyses (CDA) approachthat incorporates multimodal aspects. The study analyzes Obama's linguistic and gestural variables in the transcripts collected through interviews in the two shows. The analysis of the linguistic data applies the systemic functional linguistics approach (SFL) while the analysis of the gestural ones is done inassociation with eclectic models of non-verbal behaviors.This study has revealed the different bases of power which Obama used in his PD, the influence tactics and the types of power relations which he employed in relation to the shows’ hosts; David Letterman and Jay Leno. The study has also identified the personal, temporal and spatial deixis which Obama used to present his ideologies on domestic and international politics.The study conceptualizes frameworks in which power and ideology in PD can fit into a non-traditional context such as LNTSs in order to transfer political information to a much wider audience.